A 3D-printed surgical guide for ischemic scar targeting and ablation - Candelari, Mara; Cappello, Ida Anna; Pannone, Luigi; Monaco, Cinzia; Talevi, Giacomo; Bori, Edoardo; Ramak, Robbert; La Meir, Mark; Gharaviri, Ali; Chierchia, Gian Battista; Innocenti, Bernardo; de Asmundis, Carlo (Frontiers in Cardiovascular Medicine, 2022)
Background 3D printing technology development in medical fields allows to create 3D models to assist preoperative planning and support surgical procedures. Cardiac ischemic scar is clinically associated with malignant arrhythmias. Catheter ablation is aimed at eliminating the arrhythmogenic tissue until the sinus rhythm is restored. The scope of this work is to describe the workflow for a 3D surgical guide able to define the ischemic scar and target catheter ablation. Materials and methods For the patient-specific 3D surgical guide and 3D heart phantom model realization, both CT scan and cardiac MRI images were processed; this was necessary to extract anatomical structures and pathological information, respectively. Medical images were uploaded and processed in 3D Slicer. For the surgical guide modeling, images from CT scan and MRI were loaded in Meshmixer and merged. For the heart phantom realization, only the CT segmentation was loaded in Meshmixer. The surgical guide was printed in MED625FLX with Polyjet technology. The heart phantom was printed in polylactide with FDM technology. Results 3D-printed surgical model was in agreement with prespecified imputed measurements. The phantom fitting test showed high accuracy of the 3D surgical tool compared with the patient-specific reproduced heart. Anatomical references in the surgical guide ensured good stability. Ablation catheter fitting test showed high suitability of the guide for different ablation tools. Conclusion A 3D-printed guide for ventricular tachycardia ablation is feasible and accurate in terms of measurements, stability, and geometrical structure. Concerning clinical use, further clinical investigations are eagerly awaited.